Physiological and biochemical responses of some olive cultivars (Olea europaea L.) to water stress - Ahmadipour, Samira; Arji, Isa; Ebadi, Ali; Abdossi, Vahid (Cellular and Molecular Biology, 2018)
Water stress is one of the important abiotic environmental stresses that threaten the agricultural -products in the world. This experiment was carried out to determine the effect of water stress on physiological and biochemical characteristics of three commercial olive cultivars. A factorial pot experiment was conducted in the field conditions using completely randomized design in Gilan-Gharb city, Kermanshah province during 2015. One-year-old rooted cuttings of Zard, Amigdalolia and Konservolia olive cultivars were planted in 12-liter pots and subjected to three irrigation treatments. Irrigation treatments included control (100% of field capacity), 75% and 50% field capacity. Physiological and biochemical characteristics such as relative water content (RWC), electrolyte leakage (EL), calcium, potassium and sodium content, total phenol, malondialdehyde, peroxidases, catalase, a, b and total chlorophyll, proline and total carbohydrate were measured. Results showed that relative water content, K & Ca was reduced while sodium content increased by increasing water stress. Chlorophyll content was higher in Konservolia cultivar under water stress in comparison to the others. Water stress induced increasing in proline, total phenol and soluble carbohydrate in all cultivars. The highest total phenol and proline was recorded in Zard cultivar under water stress. Total carbohydrate increased significantly (P<0.05) in Konservolia in comparison to the others. Malondialdehyde content was increased as an index of oxidative stress by drought. The highest peroxidases and catalase activity were recorded under drought stress of 50% irrigation in Konservolia olive cultivar. Generally based on results Konservolia, Zard and Amigdalolia were more tolerant respectively.